Nationality, citizenship and integration, a european perspective - Medved, Felicita (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2001)
The article discusses the interactivity of citizenship and integration, or of membership in a state versus membership in a society. With analytical distinction between nominal and actual citizenship, the significance of the latter is analyzed as a legal tie between an individual and a state, as well as a cluster of rights and duties. The tie between citizenship and democracy is the "demos" of a political community. In a modern European nation-state, a complete separation of "ethnos" from "demos" has not been realized. Among the three prevailing integration models, the pluralistic inclusive model is the one that offers the best perspectives for the solving of tensions between immigration, integration and citizenship. It is in this context that I evaluate different meanings of integration and multiculturalism, especially its potential for actual citizenship. Within the context of developing of the concept of "civil citizenship" from the aspect of recent initiatives within the European Union, ĆdenizenshipĆ as a result of social relation with the state can be interpreted within the frames of political concept of a society in relation between political community and naturalization of an individual. In most European states there is a trend of incorporation of legally and normally inhabiting persons into civil society and state, and towards gradual liberalization of rules on naturalization, towards dilution of the "right of blood", as well as towards admission and toleration of dual multiple citizenship.
Keywords: Europe; Evropa; integracija; globalizacija; globalization; narodnost; people; državljanstvo; narodna identiteta; narodnostno vprašanje